Analisis Sentimen Acara Clash of Champions dengan Algoritma Naïve Bayes dan Support Vector Machine - Purnama, Putri Intan; Suryono, Ryan Randy (Forum Kerjasama Pendidikan Tinggi, 2025)
With the advancement of information and communication technology, it has become easier for people to exchange information and access educational content, including through online learning platforms such as Ruangguru. One of Ruangguru's flagship programs is Clash of Champions, which attracts public attention and generates various sentiments on social media. However, analyzing public sentiment towards this program faces challenges, especially due to the imbalance in the amount of data between majority and minority sentiments, which may affect the accuracy of sentiment analysis models. This study aims to compare the performance of two algorithms, namely Naïve Bayes and Support Vector Machine (SVM), in analyzing public sentiment towards this program. Using 5,226 tweets from social media X, the data was balanced using the Synthetic Minority Oversampling Technique (SMOTE) method to overcome the data imbalance problem. After the data was divided into 80% for training and 20% for testing, the results showed that before using SMOTE, Naïve Bayes had an accuracy of 78%, while SVM reached 82%. After SMOTE was applied, Naïve Bayes' accuracy increased to 79%, while SVM rose to 84%. In addition to accuracy, significant improvements were also seen in precision, recall, and f1-score, especially for positive sentiments. The results show that SVM is superior to Naïve Bayes, both in accuracy and other evaluation metrics. This research provides an in-depth understanding of the effectiveness of algorithms in sentiment analysis on entertainment-based educational programs and is expected to be a reference for the development of similar models in the future.